Genetic diversity and interspecies hybridization in Cossypha robin-chats - Munshi, Naadhirah (My University, 2017)
Southern Africa boasts a high avian diversity with five Cossypha (robin-chat) species (C. heuglini, C. caffra, C. humeralis, C. natalensis, C. dichroa) distributed at varying levels of sympatry and allopatry. Due to the effects of global anthropogenic change many species which were once ecologically separated may now overlap, leading to possible genetic introgression and hybridization. This project investigates the genetic diversity and degree of relatedness between the five Cossypha robin-chat species that occur in South Africa. Genomic DNA was extracted from blood of all five species (n=92 individuals) using the standard phenol:chloroform extraction method. Mitochondrial and nuclear markers were analyzed using Likelihood and Bayesian methods to establish phylogenetic relationships and to determine speciation patterns. MtDNA barcoding using the cytochrome c oxidase subunit 1 (CO1) gene was used to assign individuals to species. The construction of a neighbour-joining and a maximum likelihood tree provided graphic representations of the pattern of divergences between the five Cossypha species. Individuals from a species clustered together with strong bootstrap values. These procedures were accomplished using MEGA software. PopART was used to construct a minimum spanning network. This network illustrated similarity between the five species with regards to the CO1 barcode. Only seven of thirteen novel microsatellite markers were able to cross amplify in all five species. The Bayesian clustering analysis using the statistical programme STRUCTURE identified three genetic clusters (K=3) with the three distinct species being C. dichroa, C. natalensis, and C. caffra. Cossypha heuglini cluster amongst C. dichroa, C. natalensis, and C. caffra, while C. humeralis clusters amongst C. natalensis. Despite the hybridization events recorded between C. dichroa and C. natalensis these two species do not appear to be each other’s closest relatives according to microsatellite and mtDNA analysis. The hybridization events indicate their ability to overcome reproductive isolation mechanisms such as vocalisations.
A dissertation submitted to the Faculty of Science University of the Witwatersrand Johannesburg, South Africa in fulfilment of the requirements for the degree of Master of Science. June 2017
Keywords: Hybridization; Birds